Physical Activity: A Viable Way to Reduce the Risks of Mild Cognitive Impairment, Alzheimer’s Disease, and Vascular Dementia in Older Adults - Gallaway, Patrick; Miyake, Hiroji; Buchowski, Maciej; Shimada, Mieko; Yoshitake, Yutaka; Kim, Angela; Hongu, Nobuko (Brain sciences, 2017)
A recent alarming rise of neurodegenerative diseases in the developed world is one of the major medical issues affecting older adults. In this review, we provide information about the associations of physical activity (PA) with major age-related neurodegenerative diseases and syndromes, including Alzheimer’s disease, vascular dementia, and mild cognitive impairment. We also provide evidence of PA’s role in reducing the risks of these diseases and helping to improve cognitive outcomes in older adults. Finally, we describe some potential mechanisms by which this protective effect occurs, providing guidelines for future research.